Unusually delayed posttraumatic CSF rhinorrhoea - Rao, KVLN; Shukla, Dhaval; Devi, B Indira (Indian Journal of Neurotrauma, 2010)
Cerebrospinal fluid (CSF) rhinorrhoea is not uncommon after traumatic brain injury. It usually occurs within first two days of trauma and subsides spontaneously. Delayed leak beyond three months of trauma is rare. We describe a case of posttraumatic CSF rhinorrhoea which presented 44 years after injury.
Keywords: CSF leak; meningitis; trauma